2015
DOI: 10.3109/13880209.2015.1123729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the inhibitory potential ofWithania somniferaon platelet aggregation and inflammation enzymes: Anin vitroandin silicostudy

Abstract: Context Withania somnifera (L.) Dunal is traditionally used for treating various ailments, but lacks scientific evaluation. Objective This study evaluates Withania somnifera (WS) for its effect on platelet activity and inflammatory enzymes. Materials and methods Aqueous and ethanolic (1:1) leaf extracts were subjected to in vitro indirect haemolytic activity using Naja naja venom, human platelet aggregation was quantified for lipid peroxidation using arachidonic acid (AA) as agonist and 5-lipoxygenase (5-LOX) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For this study, we have chosen to investigate the proteome-wide reactivity and targets of the natural product withaferin A, a steroidal lactone from the Ayurvedic plant Withania somnifera, which has been shown to possess anti-inflammatory, anti-diabetic, and anti-cancer activity (Dar et al, 2015; Lee and Choi, 2016; Lee et al, 2016; M et al, 2016). Withaferin A bears a Michael acceptor that may react with cysteine nucleophilic hotspots in protein targets (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we have chosen to investigate the proteome-wide reactivity and targets of the natural product withaferin A, a steroidal lactone from the Ayurvedic plant Withania somnifera, which has been shown to possess anti-inflammatory, anti-diabetic, and anti-cancer activity (Dar et al, 2015; Lee and Choi, 2016; Lee et al, 2016; M et al, 2016). Withaferin A bears a Michael acceptor that may react with cysteine nucleophilic hotspots in protein targets (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Withaferin A is a natural steroidal lactone, rejuvenating tonifier, immunomodulator and a pre-dominant bioactive constituent obtained from Withania somnifera (Ashwagandha) which exhibits an array of potential biological activities including anti-inflammatory, anti-invasive, pro-apoptotic, and anti-fibrotic effects and is remarkably safe ( Vanden Berghe et al, 2012 ; Hahm et al, 2014 ; Madhusudan et al, 2016 ; Kim et al, 2017 ). WFA exhibits potent anti-inflammatory effect by downregulating central inflammatory mediator, nuclear factor kappa light chain enhancer of activated B cells (NF-κB) and other cytokines which has been well-elucidated in vitro and in vivo studies ( Heyninck et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was also reported that Withania somnifera has anti-edema and anti-myotoxic activity in cobras. Anti-hyaluronidase activity was also reported to inhibit Naja naja venom and Daboia russelii [25,26,27].…”
Section: Potential Of Activity From Withania Somnifera Compoundsmentioning
confidence: 95%